Solutions for a Singular Hadamard-Type Fractional Differential Equation by the Spectral Construct Analysis. (30th September 2020) - Zhang, Xinguang; Yu, Lixin; Jiang, Jiqiang; Wu, Yonghong; Cui, Yujun
Abstract : In this paper, we consider the existence of positive solutions for a Hadamard-type fractional differential equation with singular nonlinearity. By using the spectral construct analysis for the corresponding linear operator and calculating the fixed point index of the nonlinear operator, the criteria of the existence of positive solutions for equation considered are established. The interesting point is that the nonlinear term possesses singularity at the time and space variables.